Ways of Increasing the Activity of Commercial Banks in the Stock Market of the Republic of Uzbekistan - Ismailov, Alisher Agzamovich (Journal of Marketing and Emerging Economics, 2022)
Commercial banks are professional participants in the stock market. They, performing issuing and investment operations, at the same time provide trading and intermediary services to companies participating in the market. Therefore, the activity of commercial banks occupies an important place in the development of the stock market. The article identifies urgent problems associated with increasing the activity of commercial banks in the stock market of the Republic of Uzbekistan and develops scientific proposals aimed at solving these problems.